A Comparative Analysis of Economic Performance in Two Eras: Democratic Era (FY 89 – FY99) & Military Rule (FY00 – FY05) - Parmar, Vishnu; Azam, S. M. Shafi (JISR management and social sciences & economics, 2006)
Throughout Pakistan’s 58 year history two forms of government, namely, military and democratic rule have been imposed on the country. Although the economic and social performance of the two types of government has been documented extensively in terms of qualitative research methodology, no comprehensive quantitative model utilizing inferential statistical techniques to assess their performance has been published in current literature so far. This study attempts to develop a multi-dimensional framework of analysis to establish the statistical significance of key economic and social indicators using sample data between FY1989-FY2005. The major objective of the paper is to analyze the group means of 28 economic variables, using inferential statistical techniques, between FY1989-FY1999 and FY2000-FY2005; each period representing different types of governments. The results obtained from the quantitative analysis displays substantial statistical significance. 16 out of 28 macroeconomic variables show no significant difference in the group means of two eras and there is extremely strong evidence to support the null hypotheses formulated. Some of the main variables amongst them are: GDP growth rate, growth of investment, growth of large and small scale manufacturing, export performance, investment in health and education, balance of trade, and debt servicing.